Classification of Keruing (Dipterocarpus spp.) in Indonesia on the Basis of Fruit Characters - Dwi Tyaningsih Adriyanti; Soekotjo Soekotjo; Mochammad Na'iem; Anto Rimbawanto (Jurnal Ilmu Kehutanan)
The taxonomy status of Dipterocarpaceae family has been changed for several times. According to the review of classification compiled by Heim, Symington, Meijer, Maury and Ashton, the genus Dipterocarpus had quite close relations with Anisoptera, therefore, in some classifications they were described by writing in a group. However, Heim had a different point of view from four other experts as he divided the genus Dipterocarpus into 5 sections: sphaerales, tuberculati, angulati, alati and plicati, The classification done by Heim on Dipterocarpus were supported by Symington that the 5 sections could be detected from the fruit petals forming a tube. This study aimed to determine the position of the species in the genus of Dipterocarpus in terms of fruit characters. There were 38 species of Dipterocarpus and 3 species of Anisoptera used in the research which were collected from the natural distribution and then were identified using standard procedures, and the results were tabulated in a matrix. There were 48 characters from the entire organ, but only 9 fruit characters used in this research. Statistical analysis was done with NCSS software series 10 to build a dendrogram and to draw the hierarchical of relations between species. The results showed that the position of section in Dipterocarpus was significantly provable through morphological characters. By utilizing Anisoptera as an outgroup, it was known that Dipterocarpus of sphaerales section was closest to the Anisoptera, followed by tuberculati, angulati, alati and plicati.